(untitled) (Research, Society and Development, 2021)
Spinal metastases are etiologically characterized by hematogenous, lymphatic, CSF or direct invasion by contiguity. Breast carcinoma is the one with the greatest predilection for bone tissue, presenting an osteolytic lesion in approximately 80% of patients. The aim of the study was to describe the case report of a patient affected by a neoplastic infiltration in the spine resulting from breast adenocarcinoma, with a still unknown primary site. This is an observational study of the descriptive type, carried out through the clinical data of a patient affected by breast carcinoma, initially diagnosed with fibromyalgia, being transferred to hospitalization and diagnostic clarification. Evolved with sudden paraplegia, generalized osteolytic lesions, metastatic in nature. It was observed that even after performing the anamnesis, physical examination, multidisciplinary assessments and imaging tests, they were unable to identify the neoplastic focus of the case in question and that only after the immunohistochemically examination was it possible to identification of the primary focus in the breast. Therefore, it is essential to search for investigative methods, more specific, that help in elucidating the diagnosis, thus allowing the establishment of adequate therapy and, consequently, a better prognosis for the affected.